Electrospinning and characterization of polymer–graphene powder scaffolds. Issue 1 (2017) - Ceretti, Elisabetta; Ginestra, Paola S.; Ghazinejad, Maziar; Fiorentino, Antonio; Madou, Marc
Abstract: In this paper the morphological, mechanical and electrical characteristics of fibers electrospun from a of poly-ε-caprolactone polymer solution with different percentages of graphene nanoplatelets mixed in are reported. The morphology of the fibers was studied under optical and scanning electron microscopes to investigate the interaction of the two phases within the fibers. The scaffolds were characterized to identify the effects of the graphene on the intrinsic properties of the material. The preparation of an optimized suspension of the graphene in the solution was found to be a fundamental factor for enhancing the applicability of the resulting fibers.